EUSATfinder EUropean Space, Aerial and Terrestrial assets supporting first responders' operations - Redazione MediaGEO (GEOmedia, 2025)
The purpose of the EUSATfinder is to provide an innovative integrated and scalable solution, to support decision maker actors in real-life during different operational phases (detection, preparedness, response, recovery and mitigation of emergencies) with particular focus to first responders’ activities in situ for a disaster management.